Development of malunggay (Moringa oleifera Lam) tea - Ferrer, Famela Lynette S. (1999)
The study was conducted to produce an acceptable beverage from malunggay (Moringa oleifera Lam) leaves. The first phase of the research was the determination of the optimum drying time for the production of malunggay tea. A duration of two hours was adequate to obtain a moisture content equal to 3-4% at drying temperate of 40C. A drying time of 30 minutes at 60C was enough to dry the sample at the desired moisture content, while at 80C, drying time was only 13 minutes. For samples blanched for 3 minutes, optimum drying time at 40C was 65 minutes, 33 minutes at 60C, and 30 minutes 80C. At further blanching of 6 minutes, drying time would be 70, 23 and 14 minutes at 80C, 60C, and 40C, respectively. The second phase was the determination of optimum drying temperature - blanching time combination for the production of malunggay tea. The infusion was evaluated for color, aroma, bitterness, astringency, and tea flavor.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Tea; Malunggay